Population trends of seabirds at Stinker Point, Elephant Island, Maritime Antarctica. Issue 4 (3rd May 2018) - Petry, Maria V.; Valls, Fernanda C.L.; Petersen, Elisa S.; Finger, Júlia V.G.; Krüger, Lucas
Abstract: Available information about seabird breeding population trends on Stinker Point (Elephant Island, Maritime Antarctic Peninsula) is outdated by decades. This study reports current numbers of breeding species, and evaluates population trends over 28 years. We counted breeding pairs of seabirds along all ice-free areas on Stinker Point during two distinct periods (summers of 1985/86–1991/92 and 2009/10–2013/14). Thirteen species currently breed in the area: four Sphenisciformes, four Procellariiformes, one Suliforme and four Charadriiformes. Chinstrap penguin Pygoscelis antarcticus has the highest number of breeding pairs (4971±590), followed by gentoo penguin Pygoscelis papua (1242±339). Comparisons between the two intervals showed declining trends for almost all breeding populations, although southern giant petrels Macronectes giganteus are experiencing a subtle population growth. Population decreases in locations with low human disturbance, such as Stinker Point, may indicate sensibility to climate and environmental change and need further investigation.